Cathepsin W, T-cell receptor-associated transmembrane adapter 1, lymphotactin and killer cell lectin like receptor K1 are sensitive and specific RNA biomarkers of canine epitheliotropic lymphoma - Olayinka, Jadesola Temitope; Nagarkar, Akanksha; Ma, Diana Junyue; Wong, Neil B.; Romasco, Andrew; Piedra-Mora, Cesar; Wrijil, Linda; David, Clement N.; Gardner, Heather L.; Robinson, Nicholas A.; Hughes, Kelly L.; Barton, Bruce; et al. (Frontiers in Veterinary Science, 2023)
Cutaneous T-cell lymphoma (CTCL) is an uncommon type of lymphoma involving malignant skinresident or skin-homing T cells. Canine epitheliotropic lymphoma (EL) is the most common form of CTCL in dogs, and it also spontaneously arises from T lymphocytes in the mucosa and skin.Clinically, it can be difficult to distinguish early-stage CTCLs apart from other forms of benign interface dermatitis (ID) in both dogs and people. Our objective was to identify novel biomarkers that can distinguish EL from other forms of ID, and perform comparative transcriptomics of human CTCL and canine EL. Here, we present a retrospective gene expression study that employed archival tissue from biorepositories. We analyzed a discovery cohort of 6 canines and a validation cohort of 8 canines with EL which occurred spontaneously in client-owned companion dogs. We performed comparative targeted transcriptomics studies using NanoString to assess 160 genes from lesional skin biopsies from the discovery cohort and 800 genes from the validation cohort to identify any significant differences that may reflect oncogenesis and immunopathogenesis. We further sought to determine if gene expression in EL and CTCL are conserved across humans and canines by comparing our data to previously published human datasets. Similar chemokine profiles were observed in dog EL and human CTCL, and analyses were performed to validate potential biomarkers and drivers of disease. In dogs, we found enrichment of T cell gene signatures, with upregulation of IFNG, TNF, PRF1, IL15, CD244, CXCL10, and CCL5 in EL in dogs compared to healthy controls. Importantly, CTSW, TRAT1 and KLRK1 distinguished EL from all other forms of interface dermatitis we studied, providing much-needed biomarkers for the veterinary field. XCL1/XCL2 were also highly specific of EL in our validation cohort. Future studies exploring the oncogenesis of spontaneous lymphomas in companion animals will expand our understanding of these disorders. Biomarkers may be useful for predicting disease prognosis and treatment responses. We plan to use our data to inform future development of targeted therapies, as well as for repurposing drugs for both veterinary and human medicine.